Design of Hybrid Waveguide Structures for High-Efficiency Integrated Optical Superconducting Single Photon Detectors On Ti:LiNbO3 Waveguides - Mikhail Parfenov (IEEE, 2021)
A configuration of integrated optical superconducting single photon detectors on lithium niobate substrates based on conventional titanium in-diffused waveguides with hybrid waveguide structures for enhancing the detector efficiency is proposed and analyzed. The sensing element in the form of a meander-like superconducting nanowire from niobium nitride is covered with an additional hybrid waveguide from a dielectric material with a higher refractive index than the LiNbO3 substrate to increase the light absorption. A special mode converter in the region free from a superconducting nanostructure is used to excite a localized mode with the maximum absorption coefficient that strongly interacts with the superconductive nanostructure. Silicon and titanium dioxide are considered and compared as suitable materials for the hybrid waveguide structures. Silicon based structures give a higher light concentration and, hence, a higher absorption coefficient. However, they are very demanding to the technological accuracy. Titanium dioxide structures potentially can be produced by the standard thin-film deposition technique and contact photolithography. The estimated absorption coefficient of 1.31 dB/μm is four orders of magnitude higher than that for the detectors with a standard titanium in-diffused waveguide, and a high transformation mode efficiency opens a way for fabrication of integrated optical superconducting single photon detectors with the efficiency comparable with other competing material platforms.